2018
DOI: 10.1021/acs.iecr.8b02720
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulations of Two Phase Flow in Asymmetric Rotary Agitated Columns

Abstract: In the present work, a computational fluid dynamics (CFD) methodology has been applied to study the hydrodynamics of two phase flow in an asymmetric rotating disk contactor (ARDC) and asymmetric rotating impeller column (ARIC). The Euler–Euler model for multiphase flow and mixture k–ε model for turbulence have been used. The effect of different drag models on holdup of the dispersed phase has been investigated. The Kumar and Hartland (KH) drag model has been modified to predict the holdup accurately. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Hence, the dispersed‐phase holdup declines and reaches its minimum point. With higher agitation speed, a stronger reverse flow of the dispersed phase is prompted 39, which limits the downward flow of the droplets. This indicates that to reach the holdup minima, a higher pulsation intensity is required.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the dispersed‐phase holdup declines and reaches its minimum point. With higher agitation speed, a stronger reverse flow of the dispersed phase is prompted 39, which limits the downward flow of the droplets. This indicates that to reach the holdup minima, a higher pulsation intensity is required.…”
Section: Resultsmentioning
confidence: 99%
“…Although some simulations of accelerated droplets have been performed in liquid–air system, , experimental investigation of the drag coefficient of droplets in unsteady liquid–liquid flow is still limited. To develop a robust model for the design of the liquid–liquid extraction process, a better understanding of particle motion is required. For this reason, there is an obvious need to develop a mathematical model that describes the effect of unsteady liquid flow on the drag coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Different extraction equipment are available, such as a mixer-settler, rotating disc column, sieve-plate column, asymmetric rotating disc/impeller column, pulse disc, and doughnut column . A past study found that an asymmetric rotating impeller column (ARIC) gives the best results for the recovery of metal ions from wet phosphoric acid. Hendre et al have experimentally observed that 99% of metal ions can be extracted from the loaded phosphoric acid in ARIC . Considering the amount of solvent required for extraction, the cost of organic solvent, and the recovery of solutes, stripping of the “loaded” organic phase is an essential step in the extraction process.…”
Section: Introductionmentioning
confidence: 99%